Audio-bingeing: Storytel Originals som produkt af en streaming-kultur - Have, Iben; Jensen, Mille Raaby (Passage - Tidsskrift for litteratur og kritik, 2020)
The article discusses Storytel Original as a hybrid between digital audiobooks and TV-series. Through an interview with Mofibo’s Head of Content & Publishing in Denmark and the production Black Dolphin as a case-study, the article discusses how Storytel Original can be analysed as a TV-series in audio format from a production-, text-, and reception perspective. The first part of the article focuses on how Storytel Originals and Black Dolphin draw on institutional, distributional, narratological, and stylistic conventions known from TV-drama series. In the second part of the article, the reception and user-behavior are discussed in relation to the term bingeing. The article introduces two terms: binge-streaming and audio-bingeing. While the former suggests an extension of the term binge-watching, the latter term, audio-bingeing, narrows the perspective by accentuating specific affordances of audio-series in relation to binge-streaming.